2008
DOI: 10.1177/1528083707083794
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Copper Nanocomposite Textiles

Abstract: Fibrous textiles have been increasingly used in a variety of industries. In these applications, the surface properties of textile materials play a very important role. The surface properties of textile materials can be modified by various techniques. Copper (Cu) nanocomposite textiles are prepared by magnetron sputter coating. The nanocomposite textiles with different thickness of coatings are investigated by atomic force microscope (AFM), energy-dispersive X-ray analysis, and opto-electrical tests. The AFM ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…In the present study, the decrease observed in the tensile properties for the C60 coated fabric samples might be caused by the coarser particles accumulating on the fabric surface as the thickness increased. Coating of textiles with physical vapor deposition (PVD) methods compared to conventional methods has advantages of being environmentally friendly as it is a solvent-free application, uniform deposition of the coating, coating at low temperatures for polymeric fibers and shorter production periods [14][15][16][17].…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, the decrease observed in the tensile properties for the C60 coated fabric samples might be caused by the coarser particles accumulating on the fabric surface as the thickness increased. Coating of textiles with physical vapor deposition (PVD) methods compared to conventional methods has advantages of being environmentally friendly as it is a solvent-free application, uniform deposition of the coating, coating at low temperatures for polymeric fibers and shorter production periods [14][15][16][17].…”
Section: Resultsmentioning
confidence: 99%
“…Textile metallisation technologies, which include vacuum deposition, ion plating, electroplating and electroless plating, deposit metallic particles on the textile surface and create metallic-coated textiles (Dietzel et al 2000(Dietzel et al , 2008Akbarov et al 2005Akbarov et al , 2006Lee et al 2005;Gasana et al 2006;Jiang et al 2006Jiang et al , 2007Jiang and Guo 2008;Wei et al 2008). Coating precious metals on textile surfaces have had a long history for aesthetic or protective purposes.…”
Section: Metal Coatingmentioning
confidence: 99%
“…Wei et al (2008) reported that copper sputter coating on the surfaces of polypropylene (PP) nonwovens reduced the surface electrical resistance signifi cantly, and the resistance decreased as the coating thickness increased. Their electrical conductivity can be tailored by controlling the coating thickness and choosing the right metals.…”
Section: Metal Coatingmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the choice of polymeric material for CuNP incorporation, the synthetic method is another important aspect to consider. Many studies have reported incorporation of inorganic nanomaterials into polymers by complicated or cost-ineffective methods for antibacterial surfaces, such as coating CuNP onto polypropylene (PP) by magnetron sputter (Wei et al, 2008), attaching TiO 2 nanoparticles to fabrics by grafting with polycarboxylic acids (Meilert et al, 2005), melt-mixing silver-based nanocomposites and polymer powder (Dastjerdi et al, 2008), argon plasma grafting SiO 2 nanoparticles on wool surface (Wang et al, 2007), reducing metallic salts inside the polymeric matrix by UV irradiation (Won et al, 2004) and silver chemical plating on polyester and cotton blended fabric (Jiang et al, 2007). CuNP were embedded onto PET fabrics by a complicated three-step process: padding the fabric with chilled NaBH 4 solution, subsequent padding with metal precursor solution and curing at 180 o C for 60 seconds (Chattopadhyay and Patel, 2014).…”
Section: Introductionmentioning
confidence: 99%